New state of nanofibers in regenerative medicine. (17th February 2017) - Mohammadian, Farideh; Abhari, Alireza; Nejati-Koshki, Kazem; Akbarzadeh, Abolfazl
Abstract: Regenerative medicine has discovered engineered nanofiber scaffolds enhancing regeneration process. These agents have an attractive property to mimic the native environment. They are excellent agents in binding the extracellular matrix of a cell to another cell. They help in the growth and multiplication of the cell and help in the differentiation of the cells which are required before the regeneration process. Regenerative medicine focuses on cellular therapies, origins of stem and progenitor cells, and on explaining how they persevere (or do not) in adult organisms and improvement of biomaterials. The focus of this review is on the application of nanofiber scaffolds.